A kind of Zanthoxylum bungeanum leaf polyphenol-chitosan composite film and preparation method thereof
Patent Information
- Application Number
- CN202211248577.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-10-12
AI Technical Summary
In the prior art, chitosan has defects in the thickness, opacity, solubility, flexibility, antibacterial and antioxidant activity of biofilm, and the application of plant polyphenols on biopacking films has low opacity. Problems of uneven release and poor flexibility.
By combining polyphenols of pepper leaf with chitosan, composite film is prepared by casting film forming method, the release process of polyphenols is controlled, the antioxidant and antibacterial properties of the film are improved, and the film is improved by adjusting the ratio and process parameters. Physical performance.
It improves the antioxidant performance and antibacterial ability of the biofilm, improves the opacity and flexibility of the membrane, ensures the thickness and uniformity of the membrane, and extends the shelf life of the food.
Smart Images

Figure CN116035157B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biofilm preparation, and more particularly to a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film and a preparation method thereof. Background Art
[0002] Today, when environmental and sustainable development issues are receiving much attention, bio-based packaging materials have attracted much attention from the market and consumers because they are renewable, non-toxic and biodegradable, and can reduce white pollution and prevent food oxidation, rancidity and microbial spoilage.
[0003] Chitosan is a macromolecular compound obtained by deacetylation of chitin, which is widely found in nature. It has good film-forming properties, biocompatibility and biodegradability, can inhibit the growth and reproduction of microorganisms, prevent water loss, and can effectively extend the shelf life. However, single chitosan has certain defects in thickness, opacity, solubility, flexibility, antibacterial and antibacterial and antioxidant activity, which limits the application of chitosan in biofilms. Plant polyphenols are a general term for a class of polyhydroxy compounds found in plants, mainly flavonoids, tannins, anthocyanins, phenolic acids, etc. Experts from the World Health Organization believe that plant polyphenols are the well-deserved seventh nutrient for humans. A large number of active phenolic hydroxyl groups give them unique chemical and physiological activities, which are mainly manifested in antioxidant, antibacterial and antimicrobial effects, and the scavenging effects on various active oxygen free radicals. At present, there is a technology for embedding plant polyphenols in chitosan for the preparation of biofilms, such as tannic acid, brown algae polyphenols and tea polyphenols, but there are no reports in the prior art on the application of Zanthoxylum polyphenols to biopackaging films. Furthermore, the biofilms prepared by adding plant polyphenols such as tannic acid have low opacity and low barrier properties to visible light, resulting in uneven release of plant polyphenols, unable to ensure long-term slow release, and poor flexibility.
[0004] Therefore, how to provide a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film and a preparation method that has a good improvement effect on the film thickness, opacity and flexibility of the bio-based composite film is a problem that technicians in this field urgently need to solve. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film, which improves the antibacterial and antimicrobial and antioxidant properties of the biofilm through the combination of Zanthoxylum bungeanum leaf polyphenol and chitosan, and also has a good improvement effect on the physical properties of the biofilm, such as flexibility and opacity, and provides a new idea for the utilization of Zanthoxylum bungeanum leaves. In addition, the casting film-forming method is adopted in the film-making process, which can realize quantitative film making and ensure the thickness and uniformity of the film.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a Zanthoxylum polyphenol-chitosan composite film comprises the following steps: dissolving chitosan in an acidic aqueous solution, heating and stirring evenly, adding a Zanthoxylum polyphenol extract, homogenizing, filtering, and vacuum degassing to obtain a film solution, pouring the film solution into a mold by a pouring film-forming method, and drying to obtain the Zanthoxylum polyphenol-chitosan composite film.
[0008] The beneficial effects of the above technical scheme are as follows: Zanthoxylum leaf polyphenols have antioxidant, antibacterial and free radical scavenging properties. The use of chitosan to embed Zanthoxylum leaf polyphenol extracts can effectively control the release process of polyphenols, so that the functional active ingredients can maintain a certain concentration during food storage, effectively improving the utilization rate of the active ingredients, extending the shelf life of food, and improving the antibacterial and antibacterial ability of the biofilm; at the same time, the cross-linking effect between Zanthoxylum leaf polyphenols and chitosan improves the opacity and flexibility of the biofilm; the casting film-forming method is used to ensure the thickness and uniformity of the film.
[0009] Preferably, by weight, the ratio of chitosan to Zanthoxylum bungeanum leaf polyphenols to the acidic aqueous solution is 2g:0.5-1.0g:100mL.
[0010] The beneficial effects of the above technical solution are: the appropriate amount of added Zanthoxylum bungeanum leaf polyphenols and chitosan ensures that the active film has good light-blocking properties and flexibility.
[0011] Preferably, the acidic aqueous solution is a 1% acetic acid solution.
[0012] Preferably, the casting film forming technology is adopted, and 20 ml of the membrane solution is cast into a membrane forming device with a diameter of 9 cm, and the thickness of the prepared membrane is 39.07-41.19 μm.
[0013] The beneficial effect of the above technical solution is that the quantitative film-making method is adopted to ensure the thickness and uniformity of the film.
[0014] Preferably, the chitosan is dissolved in an acidic aqueous solution at a heating temperature of 60°C, a stirring time of 30 min, a homogenization time of 10 min at a rotation speed of 8000 r / min, filtered through a 0.45 μm filter membrane, and degassed at a vacuum degree of -0.08 MPa. The membrane solution is poured into a membrane making device, and the drying temperature is 25°C and the drying time is 24 h.
[0015] The beneficial effects of the above technical solution are: suitable process parameters for preparing the membrane ensure the structural uniformity of the active membrane and the release of Zanthoxylum bungeanum leaf polyphenols.
[0016] Preferably, the Zanthoxylum bungeanum leaf polyphenol extract contains epicatechin, chlorogenic acid, p-coumaric acid, ferulic acid, quercetin, quercetin and kaempferol.
[0017] The beneficial effect of the above technical solution is that the abundance of polyphenols in Zanthoxylum bungeanum leaves ensures good antioxidant activity of the active film.
[0018] Preferably, the Zanthoxylum bungeanum leaf polyphenol extract is prepared by the following method: dissolving Zanthoxylum bungeanum leaf powder in an ethanol solution at a solid-liquid ratio of 1:20, heating in a water bath, centrifuging to obtain the supernatant, and concentrating and purifying to obtain the Zanthoxylum bungeanum leaf polyphenol extract.
[0019] Preferably, the water bath is heated at 40° C. for 60 min; the mixture is centrifuged at 6000 r / min for 10 min; and the volume is concentrated to 25%.
[0020] Preferably, the Zanthoxylum bungeanum leaves are dried at 40° C. for 6 hours, crushed and passed through a 60-mesh sieve to obtain Zanthoxylum bungeanum leaf powder.
[0021] Preferably, Zanthoxylum bungeanum leaf polyphenols are purified by the following method: using polyamide as the stationary phase, loading the concentrated crude extract of Zanthoxylum bungeanum leaf polyphenols (1.5 BV) and maintaining it for 30 minutes, then eluting with ddH2O and 75% ethanol respectively, collecting 2 and 3 BV of the eluate, and concentrating and purifying it to obtain the Zanthoxylum bungeanum leaf polyphenols extract.
[0022] The invention also relates to a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film prepared by the method.
[0023] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention uses chitosan to embed the Zanthoxylum polyphenol extract, thereby improving the antioxidant properties of the biofilm, and through the ratio of chitosan and Zanthoxylum polyphenol and the setting of the film preparation process parameters, the biofilm's barrier effect on visible light is improved, the release of polyphenols is effectively controlled, and the shelf life of food is further extended, providing a new idea for the utilization of Zanthoxylum leaves.
[0025] (2) The casting film-forming method realizes quantitative film production and ensures the thickness and uniformity of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0027] Figure 1 Accompanying drawing is gallic acid standard curve diagram;
[0028] The regression equation is: y = 0.1463x + 0.0082, R2 = 0.9995, and has a good linear relationship in the range of 1.463 to 5.852 mg / L;
[0029] Figure 2 The attached figure is a chromatogram of component analysis of Zanthoxylum bungeanum leaf polyphenol extract;
[0030] Among them, 1 represents epicatechin; 2, chlorogenic acid; 3, catechin; 4, vanillin; 5, p-coumaric acid; 6, ferulic acid; 7, m-coumaric acid; 8, rutin; 9, o-coumaric acid; 10, quercetin; 11, quercetin; 12, naringenin; 13, kaempferol;
[0031] Figures 3a-h are scanning electron micrographs of C-film, TA / C-film and ZMP / C-film;
[0032] Figure 4 The accompanying drawings are FTIR spectra of C-film, TA / C-film and ZMP / C-film;
[0033] Figure 5 The attached drawings are XRD spectra of C-film, TA / C-film and ZMP / C-film;
[0034] Figure 6 The attached figure shows the release curves of ZMP in three different food simulation systems;
[0035] Figure 7 The attached figure shows the antioxidant activity release curve of ZMP / C-film in different food simulation systems;
[0036] Figure 8 The attached figure shows the effect of ZMP / C-film on the appearance, moisture and Vc of strawberries during storage. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] Take Zanthoxylum bungeanum leaves, dry them at 40°C for 6 hours, grind them through a 60-mesh sieve to obtain Zanthoxylum bungeanum powder, dissolve the Zanthoxylum bungeanum powder in a 60% ethanol solution at a solid-liquid ratio of 1:20 to obtain a mixed solution, water bathe the mixed solution at 40°C for 60 minutes, centrifuge the mixed solution at 6000 r / min for 10 minutes, take the supernatant and concentrate the volume to 25% to obtain a crude Zanthoxylum bungeanum polyphenol extract, use polyamide as a stationary phase, and use ddH2O and 75% ethanol as eluents, respectively, to purify the crude Zanthoxylum bungeanum polyphenol extract to obtain a Zanthoxylum bungeanum polyphenol extract (ZMP).
[0040] Weigh 2g of chitosan, dissolve it in 100ml of 1% acetic acid solution, heat and stir at 60℃ for 30min to obtain a chitosan film solution, then add 0.5g of Zanthoxylum polyphenol extract, homogenize, filter and vacuum degassing to obtain a Zanthoxylum polyphenol-chitosan film solution, use casting film forming technology to cast 20ml of the film solution into a film making device with a diameter of 9cm, dry it at 25℃ for 24h, and obtain a 0.5% Zanthoxylum polyphenol-chitosan composite film (0.5% ZMP / C-film).
[0041] Embodiment 2:
[0042] Take the chitosan film solution prepared in Example 1, add 1.0g of Zanthoxylum polyphenol extract, and obtain Zanthoxylum polyphenol-chitosan film solution after homogenization, filtration and vacuum degassing. Use casting film forming technology to cast 20ml of the film solution into a film making device with a diameter of 9cm, and dry it at 25°C for 24h to obtain 1.0% Zanthoxylum polyphenol-chitosan composite film (1.0% ZMP / C-film).
[0043] Control group 1
[0044] Take the chitosan film solution prepared in Example 1, add 1 g of glycerol, homogenize, filter and vacuum degas to obtain a control chitosan film solution, use the casting film forming technology to cast 20 ml of the film solution into a film making device with a diameter of 9 cm, and dry it at 25°C for 24 h to obtain a control chitosan film (C-film).
[0045] Control group 2
[0046] Take the chitosan film solution prepared in Example 1, add 1.0 g of tannic acid, homogenize, filter and vacuum degas to obtain a tannic acid-chitosan film solution, use the casting film forming technology, cast 20 ml of the film solution on a film making device with a diameter of 9 cm, and dry it at 25°C for 24 h to obtain a tannic acid-chitosan composite film (TA / C-film).
[0047] Determination of total phenol content in crude polyphenol extract of Zanthoxylum bungeanum leaves
[0048] The crude polyphenol extract of Zanthoxylum bungeanum leaf prepared in Example 1 was taken to measure the total phenol content, which was calculated according to the gallic acid standard curve. Figure 1 As shown in the attached figure, the total phenol content in the extracted Zanthoxylum bungeanum leaf polyphenols is 41.85 mg / g.
[0049] Analysis of components of polyphenol extract from Zanthoxylum bungeanum leaves
[0050] The polyphenol extract of Zanthoxylum bungeanum leaf prepared in Example 1 was taken, and its components were analyzed by HPLC. The chromatographic conditions were as follows: chromatographic column Symmetry C18 column (3.9 mm×150 mm, 5 μm), mobile phase 0.1% formic acid (A) and methanol (B) for gradient elution (0 min, 90% A, 10% B; 5 min, 80% A, 20% B; 10 min, 60% A, 40% B; 20 min, 50% A, 50% B; 30 min, 20% A, 80% B; 40 min, 70% A, 30% B; 50 min, 90% A, 10% B), the injection volume of the purified ZMP was 1 μL, the flow rate was 1.0 mL / min, the column temperature was 30° C., and the detection wavelength was 280 nm.
[0051] 20.00 mg of each of the 13 polyphenolic compound standards, including catechins, were accurately weighed and dissolved in methanol to prepare a 2 mg / mL stock solution, which was then prepared into a series of 1, 5, 10, 20, 40, and 60 μg / mL mixed standard solutions. After filtering through a 0.22 μm microporous filter membrane, the samples were injected and analyzed under the above chromatographic conditions. The test results are as follows: Figure 2 As shown in the attached figure.
[0052] Seven components, including epicatechin, chlorogenic acid, p-coumaric acid, ferulic acid, quercetin, quercetin and kaempferol, were detected in the polyphenol extract of Zanthoxylum bungeanum leaves, and their contents were 3.24 mg / g, 3.59 mg / g, 1.40 mg / g, 4.36 mg / g, 7.61 mg / g, 4.52 mg / g and 2.51 mg / g, respectively.
[0053] Determination of physical properties of biofilms
[0054] A control test was conducted with Examples 1 and 2 and Control Groups 1 and 2 to measure film thickness, opacity, solubility, tensile strength and elongation at break, respectively. The experimental results are shown in Table 1.
[0055] Determination of film thickness: 10 locations were randomly selected on the surface of the sample and measured using a 0-25 mm micrometer (± 0.01 mm).
[0056] Opacity determination: Using the UV method, the film was cut into 30 mm × 10 mm strips and fixed to the inner wall of the cuvette. The absorbance A was measured at a wavelength of 600 nm. An empty cuvette was used as a control. The measurement was repeated 3 times. The opacity was calculated as A divided by the film thickness d.
[0057] Solubility determination: A certain amount of the film was immersed in distilled water at 25°C for 24 hours, taken out to remove the surface moisture and placed in an oven at 105°C for 24 hours, placed in a desiccator for equilibration for 12 hours, and the mass of the film before and after drying was weighed. The solubility was calculated using formula (1).
[0058] Solubility (%) = [(m1-m2) / m1] × 100 (1)
[0059] Where m1 is the initial mass of the sample (g), and m2 is the final mass of the sample (g).
[0060] The tensile strength (TS) and elongation at break (E%) of the membrane were measured according to the method of GB / T1040.3-2006. The original gauge length was set to 100 mm, the tensile speed was set to 50 mm / min, and the maximum length and maximum tensile force of the membrane at break were measured using an electronic universal tensile machine. Each treatment was repeated 5 times. TS and E% were expressed by formula (2) and formula (3), respectively:
[0061] TS (MPa) = F / (b × d) (2)
[0062] Where F is the maximum tensile force (N), b is the sample width (mm), and d is the sample thickness (mm).
[0063] E(%)=[(L-L0) / L0]×100 (3)
[0064] Where L is the distance when the film sample breaks (mm), and L0 is the original gauge length of the film sample (mm).
[0065] Table 1 Thickness, opacity, solubility, tensile strength and elongation at break of Zanthoxylum bungeanum leaf polyphenol / chitosan composite films
[0066]
[0067]
[0068] Note: Different lowercase letters (ac) after the data in the table indicate significant differences in the data in the same column (p<0.05).
[0069] Determination of film thickness: The thickness of C-film, TA / C-film and ZMP / C-film was measured with a micrometer. The average thickness of the films was 41.42 μm. Compared with TA / C-film, ZMP / C-film showed a smaller thickness.
[0070] Determination of opacity: The opacity of the four films was measured at 600nm. There was a significant difference between TA / C-film and ZMP / C-film, indicating that the transmittance of ZMP / C-film was lower and it had a certain barrier property to visible light.
[0071] Solubility determination: The film was immersed in distilled water for 24 hours. The shape of C-film remained basically intact, while the shape of chitosan film with the addition of TA and ZMP changed to a certain extent, and the solubility was improved, but the difference was not significant.
[0072] The tensile strength (TS) and elongation at break (E%) of the film are important parameters that affect its use as packaging materials. As can be seen from the table, the tensile strength of TA / C-film and ZMP / C-film is lower than that of C-film, and the elongation at break of ZMP / C-film is significantly higher than that of TA / C-film, with extremely significant differences. This shows that the addition of Zanthoxylum bungeanum leaf polyphenols can significantly improve the flexibility of the film compared to the addition of tannic acid plant polyphenols.
[0073] Scanning electron microscopy (SEM) of biofilm
[0074] Zeiss MERLIN Compact scanning electron microscope was used for observation. A 5 mm × 5 mm film sample was taken and fixed on a copper stage after vacuum gold spraying. The surface and cross section of the sample were scanned with an electron beam with an acceleration voltage of 5 kV for electron microscope observation. The results are shown in Figures 3a-h.
[0075] From the result graph, it can be observed that the microstructure of the composite film is significantly different. From the surface scanning graph, the surface microstructure of C-film is continuous and uniform without any pores, cracks or irregularities ( Figure 3-a Different morphologies were observed for the composite membranes with TA or ZMP added. The addition of TA changed the apparent structure of the biofilm, and the surface was uneven, with some evenly dispersed white spots and raised small blocks on the surface ( Figure 3-c ), indicating that there is a certain degree of heterogeneity in the membrane matrix. After adding ZMP, the surface of 0.5% and 1.0% ZMP / C-film can be observed to be uneven and uneven, with some white spots scattered and some "small pits" ( Figure 3-e , 3-g), indicating that the addition of ZMP destroyed the network structure of the CS matrix to a certain extent, causing the discontinuity of the CS matrix, which had a certain influence on the strength of the composite membrane to withstand mechanical forces.
[0076] From the cross-sectional scan of the film ( Figure 3-b ,d,f,h), the cross section of C-film shows a loose network structure. In comparison, the cross sections of TA / C-film and ZMP / C-film are denser. The phenols and chitosan polymers may produce denser and more compact cross sections due to the mutual forces between them.
[0077] Fourier Transform Infrared Spectroscopy (FTIR)
[0078] Nicolet 670 Fourier transform infrared spectroscopy was used with a resolution of 4 cm-1, a scanning range of 4000-650 cm-1, and 64 scans to observe the changes in the internal structure of the sample. FTIR can reveal information about the molecular interactions of the chemical components of the composite membrane and is an important means of characterizing the chemical bonds in the membrane polymer. The results are shown in Figure 2. Figure 4 As shown in the attached figure, the FTIR of C-film shows typical amino polysaccharide characteristic bands, in the characteristic area, 3262-3383cm -1 The broad band is due to the stretching vibration of -OH and the symmetrical stretching vibration of -NH; 2926-2878cm -1 The peaks nearby are the vibration absorption of CH; the amide I band (1636-1771 cm -1 ), amide II band (1548-1600cm -1 ) and amide III band (1366-1404cm -1 ) correspond to C=O stretching, NH bending and CN bending respectively. In the fingerprint region, 1249cm -1 and 1152cm -1 The peaks at 1024-1074 cm are related to the symmetric and asymmetric stretching of COC; -1 The band at is caused by the stretching of the CO skeleton. When polyphenols (ZMP, TA) are added, the spectrum of the composite film is similar to that of chitosan, and no new characteristic absorption bands are found. These results show that the addition of TA or ZMP is not enough to cause significant changes in the chitosan structural matrix, but the changes in the FTIR absorption peak intensity and the mechanical properties of the composite film reveal the cross-linking effect between chitosan and TA or ZMP molecules.
[0079] X-ray diffraction spectroscopy
[0080] The effect of ZMP on the crystal properties of chitosan composite membranes was investigated by using a D / max 2550 X-ray powder diffractometer at a voltage of 40 kV, a current of 100 mA, a scanning range of 10° to 80°, and a scanning rate of 5° / min. Figure 5As shown in the attached figure. The C-film-based composite film has two diffraction peaks near the Bragg angle (2θ) of 11.6° and 22.1°. According to previous literature reports, the diffraction peak around 11.6° reflects the hydrated crystal structure of the chitosan film, while the diffraction peak around 22.1° reflects the amorphous structure of the chitosan film, which is the characteristic fingerprint of chitosan. After adding ZMP to chitosan, the two diffraction peaks gradually become flat, and the diffraction intensity decreases, especially the characteristic peak at 22.1°; the addition of TA also has the same effect. It can be seen that ZMP or TA induces the chitosan film to transform from amorphous structure to amorphous structure, which reduces the crystallinity of the composite film. In TA / C-film and ZMP / C-film, due to the competitive effect of hydrogen bonds between chitosan and polyphenols, the interaction between polyphenols and chitosan may hinder the formation of hydrogen bonds within or between chitosan molecules, resulting in the further formation of amorphous complexes in the structure, reduced crystallinity, increased solubility, and increased film-forming properties of chitosan.
[0081] Polyphenol release kinetics
[0082] Water, 3% (v / v) acetic acid, and 10% (v / v) ethanol were used to simulate aqueous, acidic, and alcoholic foods, and the release process of polyphenols from 1.0% (m / v) ZMP / C-film composite films in food simulant solutions was investigated. The film samples were cut into 1 cm × 1 cm pieces, weighed, and placed in volumetric flasks containing 20 mL of simulated solution, and released at 25°C in the dark for 48 h; 0.3 mL of the above release solution was taken at different time points (the same amount of simulated solution was added to the volumetric flask in time), mixed with 0.3 mL of Folin reagent, and allowed to stand for 5 min, and 0.6 mL of Na2CO3 (10%, v / v) was transferred to the mixture, and the volume was adjusted to 3 mL. After color development at 25°C in the dark for 2 h, the absorbance (A760 nm) was measured, and the total polyphenol content was calculated from the gallic acid standard curve in 1.3.1, expressed as milligrams of gallic acid equivalent per gram of sample (mg GAE / g film). The experiment was repeated 3 times, and the cumulative release rate of polyphenols was calculated according to formula (4):
[0083] Cumulative release rate (%) = (m t / m0)×100 (4)
[0084] Where: Mt is the cumulative release of polyphenols at time t (μg), M0 is the total polyphenol loading (μg) Figure 6As shown in the attached figure. In each simulated food system, all films have similar release curves, with a fast release rate at the beginning and then slowing down. The time taken for ZMP to reach equilibrium in the three systems of water, 3.0% acetic acid and 10% ethanol was 720min, 540min and 1440min respectively, and the release of ZMP in the acidic food simulation system was higher than that in the aqueous and alcoholic food simulation systems (p<0.05). This shows that the ZMP / C-film film has the highest solubility in acidic media. The release of polyphenols from the polymer matrix is related to many factors, such as the properties of the polymer itself (swelling, molecular weight distribution, density, size, etc.), the properties of the polyphenols themselves (molecular size, shape, density, polarity and solubility, etc.) and factors related to the interaction between the polymer matrix and the polyphenols (plasticization, anti-plasticization, etc.). In this study, the high solubility of chitosan in acidic medium will lead to the dissociation of hydrogen bonds between amino groups and phenolic groups, thereby promoting the entry of acetic acid solvent into the membrane matrix and increasing the release rate of ZMP; in addition, the polyphenol release rate depends on the ZMP distribution coefficient between the organic phase and the aqueous phase. ZMP is slightly soluble in water, and the ZMP distribution coefficient in 10% acetic acid volume is larger than that in aqueous simulated liquid. From the above analysis, it can be inferred that the release process of ZMP may be that the system solution penetrates into the matrix, causing the polymer skeleton to swell, the free volume to increase, and the polymer cross-linked network structure to become wider. After that, the amorphous polyphenols dissolved in the chitosan polymer matrix diffuse into the entire polymer network space and migrate to the external solution system. It can be seen that the release of polyphenols from ZMP / C-film is affected by the polarity and pH of the environmental system, and the release amount is the largest in acetic acid solution.
[0085] Antioxidant Capacity
[0086] The antioxidant capacity of the 1.0% ZMP / C-film release solution was determined by measuring the scavenging rate of DPPH and ABTS+ free radicals. Figure 7 As shown in the attached figure, the antioxidant activity of the composite film is positively correlated with the release time. The scavenging effects of the ZMP / C-film membrane under different food simulation systems are significantly different (p<0.05). The membrane has the strongest antioxidant capacity in the 3% acetic acid system, with DPPH and ABTS+ free radical scavenging rates of 73.25% and 81.06%, respectively, which are 0.83 times and 0.82 times that of 1 mg / mL Vc under the same conditions; the lowest free radical scavenging rate was shown in 10% ethanol solution, which is basically consistent with the results of the ZMP release rate study.
[0087] Study on the preservation of strawberry with ZMP / C-film
[0088] Fresh strawberries were collected from a farm in Yuci, Shanxi Province. Samples with the same color, size, weight and maturity were selected and divided into three groups (n=15): untreated control, C-film, and ZMP / C-film. The strawberries were placed in a 4L polystyrene container, and the container mouth was covered with ZMP / C-film. The samples were kept at 25°C and 50% relative humidity for 7 days. The weight loss rate and vitamin C (Vitamin C, Vc) were measured at 0, 1, 2, 3, 4, 5, 6, and 7 days, respectively. Each group of fresh-keeping tests was repeated three times.
[0089] The weight loss rate is calculated according to formula (11):
[0090]
[0091] Where: m0 is the weight of strawberries on day 0 of storage; mt is the weight of strawberries at different storage time periods.
[0092] For determination of Vc content, 10 g of ground strawberry pulp was diluted to 20 mL with 1.0 mol / L HCl solution, vortexed for 5 min, centrifuged at 7500 r / min at 4°C for 5 min, filtered through a 0.45 μm filter membrane, and the supernatant was taken for absorbance determination, and calculated according to the standard Vc standard curve equation.
[0093] Results and Analysis:
[0094] As attached Figure 8 -A shows that the strawberries in the control group (CK) began to lose their luster and moisture on the second day, withered and turned black on the fourth day, and rotted on the fifth day. No obvious changes were found in the appearance of the strawberries covered with film for preservation. The weight and Vc changes of the three groups of strawberries at different storage times were significantly different (p<0.05). As the storage time increased, the weight loss of the three groups of strawberries gradually increased (see Appendix Figure 8 -B), the weight loss rate of strawberries in the control group without film coverage was significantly higher than that in the treated group. The film can effectively prevent the water content of the strawberry samples in the container from diffusing to the external environment. After 7 days of storage, the weight loss rate of strawberries treated with ZMP / C-film (4.85%) was significantly lower than that of strawberries not covered with film (15.47%) and that of the C-film treated group (6.33%). Adding ZMP to C-film can significantly reduce the weight loss of strawberries, which may be related to the denser structural properties of ZMP / C-film (see SEM results), which inhibits the diffusion of water content of strawberries to the external environment.
[0095] Vitamin C is an important indicator of fresh fruit. Figure 8-C shows that the Vc content of the three groups of strawberries showed a downward trend during storage. The Vc content of the strawberries treated with ZMP / C-film slowly decreased from 712.77 mg / kg to 546.84 mg / kg on the 7th day, but was higher than the 513.16 mg / kg of the C-film treated group and the 314.62 g / kg of the strawberries in the uncovered treatment group. In comparison, the CK group decreased significantly, while the ZMP / C-film and C-film treated groups decreased slowly, especially the ZMP / C-film. The loss of strawberry Vc is related to its own respiration, external oxidation and microbial corruption during storage. The most likely reason is that the presence of oxygen promotes the oxidative loss of strawberry vitamins. The chitosan film blocks the strawberry from contacting with oxygen, inhibiting the oxidative loss of Vc. The release of polyphenols in ZMP / C-film can prevent Vc from being oxidized, thereby more effectively protecting the quality of strawberries.
[0096] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0097] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film, characterized in that: The method comprises the following steps: dissolving chitosan in an acidic aqueous solution, heating and stirring the solution, adding a Zanthoxylum polyphenol extract, homogenizing, filtering and vacuum degassing to obtain a membrane solution, pouring the membrane solution into a mold by a pouring film forming method, and drying to obtain a Zanthoxylum polyphenol-chitosan composite membrane; The ratio of chitosan, Zanthoxylum bungeanum leaf polyphenol extract and acidic aqueous solution is 2g: 0.5-1.0g: 100mL; The Zanthoxylum bungeanum leaf polyphenol extract contains epicatechin, chlorogenic acid, p-coumaric acid, ferulic acid, quercetin, quercetin and kaempferol.
2. The method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film according to claim 1, characterized in that: The acidic aqueous solution is a 1% acetic acid solution.
3. The method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film according to claim 1, characterized in that: The casting film forming technology was used to cast 20 ml of the membrane solution into a mold with a diameter of 9 cm, and the mold was a membrane maker. The thickness of the prepared membrane was 39.07 ~ 41.19 μm.
4. The method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film according to claim 1, characterized in that: The heating temperature of chitosan dissolved in acidic aqueous solution is 60°C, and the stirring time is 30 minutes; after adding the polyphenol extract of Zanthoxylum bungeanum leaves, the homogenization time is 10 minutes at a speed of 8000 r / min; the pore size of the filter membrane is 0.45 μm; the degassing vacuum degree is -0.08MPa; after the membrane solution is poured into the mold, the drying temperature is 25°C and the drying time is 24 hours; the mold is a membrane making device.
5. The method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film according to claim 1, characterized in that: The Zanthoxylum bungeanum leaf polyphenol extract is prepared by the following method: dissolving Zanthoxylum bungeanum leaf powder in an ethanol solution at a solid-liquid ratio of 1:20, heating in a water bath, centrifuging to obtain the supernatant, and concentrating and purifying to obtain the Zanthoxylum bungeanum leaf polyphenol extract.
6. The method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film according to claim 5, characterized in that: The water bath was heated at 40°C for 60 min; the mixture was centrifuged at 6000 r / min for 10 min; and the volume was concentrated to 25%.
7. The method for preparing a Zanthoxylum bungeanum leaf polyphenol-chitosan composite film according to claim 5, characterized in that: The polyphenol extract of Zanthoxylum bungeanum leaf was purified by the following method: using polyamide as the stationary phase, 1.5 BV of the concentrated crude polyphenol extract of Zanthoxylum bungeanum leaf was loaded and maintained for 30 min, then eluted with ddH2O and 75% ethanol, respectively, and 2 BV and 3 BV eluates were collected respectively, and the polyphenol extract of Zanthoxylum bungeanum leaf was concentrated and purified.
8. The Zanthoxylum bungeanum leaf polyphenol-chitosan composite film prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Edible chitosan green tea polyphenol active packaging film material and its preparation method
CN103087356A